2017
DOI: 10.1002/path.4858
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic signatures reveal a dualistic and clinically relevant classification of anal canal carcinoma

Abstract: Aetiologically linked to HPV infection, malignancies of the anal canal have substantially increased in incidence over the last 20 years. Although most anal squamous cell carcinomas (SCCs) respond well to chemoradiotherapy, about 30% of patients experience a poor outcome, for undetermined reasons. Despite cumulative efforts for discovering independent predictors of overall survival, both nodal status and tumour size are still the only reliable factors predicting patient outcome. Recent efforts have revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…Sections of intestinal villi with massive amyloidosis were chosen for LMD‐based microproteomic analysis to characterize the type of amyloidosis. Characterization was performed using a recently developed method for proteomic analysis of small laser‐microdissected formalin‐fixed, paraffin‐embedded (FFPE) samples . The procedure for LMD‐based microproteomics has been described previously and uses in‐solution tryptic digestion of proteins directly from tissue pieces.…”
Section: Methodsmentioning
confidence: 99%
“…Sections of intestinal villi with massive amyloidosis were chosen for LMD‐based microproteomic analysis to characterize the type of amyloidosis. Characterization was performed using a recently developed method for proteomic analysis of small laser‐microdissected formalin‐fixed, paraffin‐embedded (FFPE) samples . The procedure for LMD‐based microproteomics has been described previously and uses in‐solution tryptic digestion of proteins directly from tissue pieces.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical analysis was performed with a standard protocol detailed previously. 54 Based on epithelial vimentin expression, the tissue samples were classified into two groups: EMT-positive versus EMT-negative. Regarding PD-L1 immunoreactivity in epithelial (tumor) cells, a semi-quantitative score of the intensity (0: negative; 1: low; 2: moderate; 3: strong) and extent (0: <5% of positive cells; 1: 6-33%; 2: 34-66%; 3: >67%) of the staining according to an arbitrary scale was used.…”
Section: Tissue Samples Immunohistochemistry and Immunostaining Assementioning
confidence: 99%
“…In a recent study on breast cancer, we could show that the identification of more than 1400 proteins was possible on <3000 cells . Since then, LMD‐microproteomics has been successfully applied for biomarker discovery in cancer and for the investigation of proteomic changes in tissues infected by parasites . In a recent study, we demonstrated that it could be combined with MALDI imaging data to identify proteins related to ITH .…”
Section: Four Key Workflows For Diagnostic Proteomic Analysesmentioning
confidence: 99%